National Immunization Campaigns with Oral Polio Vaccine Reduce All-Cause Mortality: A Natural Experiment within Seven Randomized Trials - Andreas Andersen; Ane Baerent Fisker; Amabelia Rodrigues; Cesario Martins; Henrik Ravn; Henrik Ravn; Najaaraq Lund; Sofie Biering-Sørensen; Christine Stabell Benn; Christine Stabell Benn; Peter Aaby; Peter Aaby; et al. (Frontiers Media S.A., 2018)
BackgroundA recent WHO review concluded that live BCG and measles vaccine (MV) may have beneficial non-specific effects (NSEs) reducing mortality from non-targeted diseases. NSEs of oral polio vaccine (OPV) were not examined. If OPV vaccination campaigns reduce the mortality rate, it would suggest beneficial NSEs.SettingBetween 2002 and 2014, Guinea-Bissau had 15 general OPV campaigns and other campaigns with OPV plus vitamin A supplementation (VAS), VAS-only, MV, and H1N1 vaccine. In this period, we conducted seven randomized controlled trials (RCTs) with mortality as main outcome.MethodsWithin these RCTs, we assessed whether the mortality rate was lower after-campaign than before-campaign. We used Cox models with age as underlying time and further adjusted for low birth-weight, season and time trend in mortality. We calculated the adjusted mortality rate ratio (MRR) for after-campaign vs before-campaign.ResultsThe mortality rate was lower after OPV-only campaigns than before, the MRR being 0.81 (95% CI = 0.68-0.95). With each additional dose of campaign-OPV the mortality rate declined further (MRR = 0.87 (95% CI: 0.79-0.96) per dose) (test for trend, p = 0.005). No other type of campaign had similar beneficial effects. Depending on initial age and with follow-up to 3 years of age, the number needed to treat with campaign-OPV-only to save one life was between 68 and 230 children.ConclusionBissau had no case of polio infection so the results suggest that campaign-OPV has beneficial NSEs. Discontinuation of OPV-campaigns in low-income countries may affect general child mortality levels negatively.